Development Impact Analysis Of The Improvement Of Basic Infrastructures Welfare Society In Village Kiren Bonggo Sarmi District - Tebay, Vince; Korwa, Ferry (Advances in Social Sciences Research Journal, 2017)
Based on analysis of the processed data and on research based on the variable first and second variable that impacts the development of Basic Infrastructure Improvement Against Public Welfare. From the construction of roads and bridges have a positive impact on the Education, Health and Economic Income society. Due road and bridge the basic facilities needed by the public to access a wide range activities in education, health, and livelihoods of others. In addition to the construction of roads and bridges, clean water is Also a basic need that is in need by the community in Kiren Village. But until now the Development of clean water tub in Kiren Village has not done well. Now the people in Kiren Village still use the water borehole and Rainwater for consumption. Due to the impact of the construction of clean water bath, influence on people's lives in Kiren Village. Until now, people who are at Kiren Village still hope that the government can build a clean water bath at Kiren Village. In addition to road and bridge construction, as well as the Clean Water community in Kiren Village Also expect Reviews their hometown of adequate lighting. Until now, people still use diesel power for lighting villages in each lane at Kiren Village. Also Kiren Village lighting is impacting on Education, Health, and Economic Income society. Then the activities conducted in the evenings such as learning, good lighting IS ALSO Reviews their very helpful nurses and other health workers to work in the evening as night striker duty to keep the patient. In addition to health education in economics lighting darting Also in need, with good lighting community can the make ice cubes, made cakes, and various other activities at night. If people's basic needs such as roads and bridges, Water Supply and Lighting. Perform well then Welfare Society in Kiren Village would be good. This study uses a method of describing the nature of an ongoing state of current research is conducted, and the search for the causes of a phenomenon / phenomena to be studied and made any particular conclusion (Husein Umar, 1999: 20).